A New Path Forward in South Sudan - Rashid, Shahidur (2012)
IFPRI Policy Seminar "A New Path Forward: Agriculture and Food Security Strategy for South Sudan" at IFPRI on 23 October 2012 by Shahidur Rashid, IFPRI.